The role of parents in the prevention of bullying: learning to resolve conflicts in the family (Journal of Parents and Teachers, 2018)
School mediation is an essential resource to prevent bullying, but we must place more emphasis on the fundamental role of parents in this matter.
Keywords: mediation; bullying; prevention; harassed stalker; conflict